Ultra-Sensitive TP53 Sequencing for Cancer Detection Reveals Progressive Clonal Selection in Normal Tissue over a Century of Human Lifespan - Salk, Jesse J.; Loubet-Senear, Kaitlyn; Maritschnegg, Elisabeth; Valentine, Charles C.; Williams, Lindsey N.; Higgins, Jacob E.; Horvat, Reinhard; Vanderstichele, Adriaan; Nachmanson, Daniela; Baker, Kathryn T.; Emond, Mary J.; Loter, Emily; et al. (Cell reports (Cambridge), 2019)
High-accuracy next-generation DNA sequencing promises a paradigm shift in early cancer detection by enabling the identification of mutant cancer molecules in minimally invasive body fluid samples. We demonstrate 80% sensitivity for ovarian cancer detection using ultra-accurate Duplex Sequencing to identify TP53 mutations in uterine lavage. However, in addition to tumor DNA, we also detect low-frequency TP53 mutations in nearly all lavages from women with and without cancer. These mutations increase with age and share the selection traits of clonal TP53 mutations commonly found in human tumors. We show that low-frequency TP53 mutations exist in multiple healthy tissues, from newborn to centenarian, and progressively increase in abundance and pathogenicity with older age across tissue types. Our results illustrate that subclonal cancer evolutionary processes are a ubiquitous part of normal human aging, and great care must be taken to distinguish tumor-derived from age-associated mutations in high-sensitivity clinical cancer diagnostics. [Display omitted] •Ovarian cancer can be detected by ultra-accurate sequencing of uterine lavage DNA•However, low-frequency TP53 mutations also exist in normal tissue of healthy women•TP53 mutations are increasingly selected for with age, revealing somatic evolution•Age-associated, cancer-like mutations challenge specificity for cancer detection Salk et al. demonstrate that ultra-sensitive DNA sequencing to identify TP53 mutations among cells shed into uterine fluid shows potential for minimally invasive ovarian cancer detection. Yet they also reveal ubiquitous age-related accumulations of cancer-like TP53 mutations in the normal tissues of healthy women. This highlights an important challenge of using tumor driver mutations for cancer screening.